Energy storage ceramic material prepared from shells, method and green refrigeration equipment

By using marine solid waste such as shells to prepare high-temperature and durable honeycomb structure ceramic materials, combined with solar energy and low-trough electric drive, the problems of high energy consumption and inapplicable energy storage materials in marine cold chain storage and transportation are solved, and efficient and environmentally friendly green refrigeration effect is achieved .

CN119320623APending Publication Date: 2025-01-17SANYA SCI & EDUCATION INNOVATION PARK WUHAN UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411361753.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The existing marine cold chain storage and transportation technology consumes high energy and has high environmental pollution. Conventional energy storage materials are not suitable for high-temperature refrigeration needs, and the refrigeration equipment is costly and low efficiency.

Method used

Shells, discarded soil, sludge and diatomaceous earth are used to prepare high-temperature and durable honeycomb structure ceramic skeletons, and energy storage density is increased by encapsulating molten salt, combined with solar energy and low-trough electric drive, green refrigeration equipment is designed to achieve efficient refrigeration.

Benefits of technology

The green refrigeration effect of high-temperature heat storage capacity, long life, low cost and low carbon emissions has been achieved, reducing refrigeration costs and significantly reducing carbon emissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320623A_ABST
    Figure CN119320623A_ABST
Patent Text Reader

Abstract

The invention relates to an energy storage ceramic material prepared from shells, a method and green refrigeration equipment. The energy storage ceramic material comprises a ceramic skeleton containing honeycomb holes and fused salt packaged in part of the honeycomb holes of the ceramic skeleton through a packaging agent. Wherein the raw materials of the ceramic skeleton comprise a main material and a binder accounting for 2-6% of the mass of the main material; the main materials comprise the following components in percentage by mass: 68-80% of a mixture, 2-6% of a lubricant and 14-30% of water; the mixture comprises shells, spoil, sludge and diatomite. The obtained energy storage ceramic material is high in unit volume heat storage capacity and large in molten salt phase change latent heat, and a long-time constant-temperature heat source can be provided; fused salt is uniformly packaged in only part of honeycomb holes, the rest of honeycomb holes are still through holes, heat convection and heat release are facilitated, the heat exchange efficiency is improved, and the energy storage ceramic material is of a honeycomb structure, can stably work for a long time, is long in service life and is low in refrigeration cost when being used in green refrigeration equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of energy storage ceramics, and in particular to an energy storage ceramic material and method prepared by using shells, and green refrigeration equipment. Background Art

[0002] With the expansion of the global marine cold chain market and global warming, the energy consumption and carbon emissions of the marine cold chain are becoming increasingly serious. At present, the cold chain storage and transportation of marine fisheries and fruits and vegetables mainly rely on fossil energy or conventional electricity to make ice and cold boxes and cold storage. When used, it consumes a lot of energy and causes great environmental pollution. It consumes a lot of energy and generates huge carbon emissions. In addition, the storage and transportation costs are high, the operation is complicated, it takes a long time, and the efficiency is low.

[0003] In recent years, environmentally friendly, energy-saving and low-cost refrigeration technology and equipment have become the focus of expert research. For example, the utility model patent "An environmentally friendly and energy-saving heating and refrigeration equipment" (CN212299486U) discloses an advanced refrigeration equipment using solar collectors, which can achieve heating and refrigeration at the same time, has a simple structure, and is energy-saving and environmentally friendly; but the patent uses a water tank to store heat, that is, water with a lower heat storage density is used as the heat storage medium, and the storage capacity is small, resulting in a large equipment volume, low heat utilization efficiency, and high cost; the utility model patent "Waste heat refrigeration equipment" (CN205536660U) discloses a refrigeration technology equipment that uses factory waste heat steam and uses medium water for refrigeration, which has the characteristics of energy saving and emission reduction, easy operation and easy maintenance, but it uses high-temperature and high-pressure steam generated by industrial waste heat, and has no heat storage device, which will cause heat temperature fluctuations, refrigeration effect fluctuations, and limited usage scenarios. The Chinese invention patent "A method for preparing an inorganic phase-change thermal insulation building material" (CN106167372A) uses clam shells and sodium sulfate decahydrate as raw materials to prepare an inorganic phase-change thermal insulation building material that can effectively store and release heat. However, since the invention uses crushed shell powder as a raw material for a low-temperature chemical synthesis method to prepare the thermal storage material, it is only suitable for thermal storage and cooling of the interior and exterior walls of buildings with low ambient temperatures (such as room temperature to about 60°C) and fixed locations, and it is difficult to withstand higher temperatures; and the preparation cost is usually high.

[0004] Therefore, the cold chain market, which consumes huge amounts of energy, urgently needs to avoid consuming precious conventional electricity and use waste electricity and cheap electricity such as solar energy, wind energy and off-peak electricity as much as possible. At the same time, it also needs to use highly reliable and long-life energy storage materials and equipment to carry out continuous, efficient and low-cost refrigeration to achieve the goal of green and environmental protection. Summary of the invention

[0005] The purpose of the present invention is to overcome the above-mentioned technical deficiencies, to provide an energy storage ceramic material and method prepared using shells and green refrigeration equipment, to solve the technical problems in the prior art of high energy consumption of refrigeration equipment and the unsuitability of conventional energy storage materials for cold chain storage and transportation.

[0006] In order to achieve the above technical purpose, the technical solution provided by the present invention is: In the first aspect, the present invention provides an energy storage ceramic material prepared using shells, comprising a ceramic skeleton containing honeycomb pores, and molten salt encapsulated in the honeycomb pores of the ceramic skeleton by an encapsulant; wherein the raw materials of the ceramic skeleton include a main material and a binder accounting for 2 to 6% of the mass of the main material; in terms of mass percentage, the main material includes 68 to 80% of a mixture, 2 to 6% of a lubricant and 14 to 30% of water; the mixture includes shells, abandoned soil, sludge and diatomaceous earth.

[0007] In a second aspect, the present invention provides a method for preparing energy storage ceramic materials using shells, comprising the following steps: (1) taking dry powders of shells, waste soil, sludge and diatomaceous earth in proportion and mixing them uniformly to obtain a mixture, adding a binder, a lubricant and water to the mixture, kneading and aging to obtain a plastic clay material; (2) using an extrusion molding method to make the plastic clay material into a honeycomb green body, drying and firing to obtain a ceramic skeleton containing honeycomb holes; (3) uniformly selecting a portion of the honeycomb holes in the ceramic skeleton as packaging holes, coating one end of the packaging hole with a packaging agent, and then injecting molten salt into the packaging hole, and then coating the other end of the packaging hole with a packaging agent to obtain a ceramic-molten salt composite; (4) the ceramic-molten salt composite is subjected to heat treatment to obtain an energy storage ceramic material.

[0008] In a third aspect, the present invention provides a green refrigeration equipment, including an electric power system, a ceramic heat storage system and a thermal energy release refrigeration system; wherein the electric power system is used to input solar photovoltaic power generation during the day or valley electricity at night into the ceramic heat storage system; the ceramic heat storage system includes a thermal insulation layer and an insulating layer arranged in sequence from the outside to the inside, and a plurality of electric heating elements and energy storage ceramic materials are evenly and cross-arranged inside the insulating layer, and the electric heating elements are connected to the electric power system; the energy storage ceramic materials are connected to the thermal energy release refrigeration system through a heat exchanger, and the thermal energy release refrigeration system is used to convert thermal energy into refrigeration kinetic energy.

[0009] Compared with the prior art, the beneficial effects of the present invention include: The present invention utilizes the natural porous structure of shells, and is equipped with porous materials such as diatomite, so that the fired energy storage ceramic skeleton matrix is ​​dense and porous in structure, and then by encapsulating molten salt, its high-temperature heat storage capacity is effectively improved. The obtained energy storage ceramic material has a high unit volume heat storage capacity, and the molten salt phase change latent heat is large, which can provide a long-term constant temperature heat source; the present invention only uniformly encapsulates molten salt for part of the honeycomb holes, and the remaining part is still a through hole, which is conducive to convective heat exchange to release heat and improve heat exchange efficiency, and the energy storage ceramic material has a honeycomb structure, can work stably for a long time, and has a long life. The energy storage ceramic material of the present invention is used in green refrigeration equipment, which is expected to consume solid wastes such as discarded shells and abandoned soil on a large scale, and at the same time, it can enable green refrigeration equipment to have a larger refrigeration capacity without occupying a large area, reduce investment and land occupation, and can effectively use solar energy and valley electricity as the main driving energy, with low refrigeration cost, effectively reducing carbon emissions. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 It is a structural schematic diagram of the green refrigeration equipment of the present invention; Among them: 1-power system; 2-ceramic heat storage system; 3-heat energy release refrigeration system; 101-power input device; 201-insulation layer; 202-insulation layer; 203-electric heating element; 204-energy storage ceramic material encapsulating molten salt; 205-heat exchanger; 301-fan; 302-refrigeration device; 303-water replenishment device; 304-water purification device; 305-circulation pump; Figure 2 is the phase composition XRD spectrum of the energy storage honeycomb ceramic material (Example 1) of the present invention; Figure 3 This is a SEM scanning electron microscope photograph of the matrix of the energy storage honeycomb ceramic material (Example 1) of the present invention. DETAILED DESCRIPTION

[0011] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0012] At present, the cold chain storage and transportation of marine fisheries and fruits and vegetables mainly rely on fossil energy or conventional electricity to make ice cubes and store them in cold boxes and cold storages, while the existing refrigeration equipment usually does not have a heat storage device or uses water with a lower heat storage density as the heat storage medium, resulting in fluctuations in the refrigeration effect or small energy storage, low heat utilization efficiency and high cost. In view of the above problems, the present invention provides an energy storage ceramic material and method prepared by shells and green refrigeration equipment.

[0013] Among them, the present invention provides an energy storage ceramic material, which is a high-temperature resistant energy storage honeycomb ceramic material that can be used for temperatures above 800°C, prepared by using cheap marine solid waste such as shells, waste soil generated by excavation of construction foundation pits, and solid waste resources such as sludge generated by cleaning and dredging rivers, as well as low-grade diatomaceous earth. The energy storage ceramic material is then used to manufacture a new type of solar energy-valley electricity complementary high-efficiency energy storage green refrigeration equipment; compared with refrigeration equipment that uses conventional electricity all day, the refrigeration equipment of the present invention has higher thermal utilization efficiency, lower cost, higher operating reliability, longer life, stable refrigeration effect, and significant environmental benefits.

[0014] In a first aspect, the present invention provides an energy storage ceramic material prepared by using shells, comprising a ceramic skeleton containing honeycomb pores, and a molten salt encapsulated in the honeycomb pores of the ceramic skeleton by an encapsulant; Among them, the raw materials of the ceramic skeleton include a main material and a binder accounting for 2-6% of the mass of the main material; in terms of mass percentage, the main material includes 68-80 wt% of a mixture, 2-6 wt% of a lubricant and 14-30% of water; the mixture includes shells, abandoned soil, sludge and diatomaceous earth.

[0015] Preferably, the mixture includes, by mass percentage, 10-80 wt% of shells, 5-30 wt% of waste soil, 5-30 wt% of sludge, and 10-80 wt% of diatomaceous earth; each raw material in the mixture is a dry powder after passing through a 250-mesh sieve.

[0016] Further preferably, the mixture includes, by mass percentage, 45-50 wt% of shells, 7.5-15 wt% of waste soil, 7.5-10 wt% of sludge, and 25-35 wt% of diatomaceous earth.

[0017] Preferably, the pore density of the honeycomb pores in the ceramic skeleton is 70-80%.

[0018] Preferably, the molten salt includes one or more of Na2SO4 / NaCl molten salt, LiF / MgF2 molten salt and Li2CO3 / Na2CO3 molten salt.

[0019] Preferably, 50-67% of the honeycomb pores in the ceramic skeleton are uniformly selected to inject molten salt for packaging; in a single honeycomb pore, the injected volume of the molten salt is 85-92% of the volume of the honeycomb pore.

[0020] Preferably, the encapsulant is a composite of 70-80% ferrotitanium slag and 20%-30% Al(H2PO4)3 aqueous solution, and the concentration of the Al(H2PO4)3 aqueous solution is 40-50wt%; the coating thickness of the encapsulant is 3-7mm.

[0021] Preferably, in terms of the mass percentage of oxides, the main component of the shell is CaO: 40-60 wt%, and the loss on ignition is 40-60 wt%; the main component of the abandoned soil is SiO2: 50-60 wt%, Al2O3: 15-25 wt%, CaO: 7-9 wt%, Fe2O3: 2-3 wt%, MgO: 3-4 wt%, K2O: 1-2 wt%; the main component of the sludge is SiO2: 50-70 wt%, Al2O3: 5-20 wt%, and the loss on ignition is 30-50 wt%; the main component of diatomite is SiO2: 75-95 wt%, Al2O3: 5-25 wt%, and Fe2O3: 0-5 wt%. The present invention prepares an calcium feldspar honeycomb ceramic material with a porous structure by combining these four raw materials to produce a physical and chemical reaction at high temperature, and provides a carrier for encapsulating and adsorbing molten salt phase change materials. Moreover, the grade of each raw material has relatively little impact. For example, the heat storage performance of the energy storage ceramic material made of diatomaceous earth with a SiO2 grade of 84.69 wt% is slightly different from that of the energy storage ceramic material made of high-grade (first-grade 90% or more SiO2) diatomaceous earth. However, high-grade raw materials are usually more expensive. Therefore, the present invention can select common lower-grade raw materials as needed to reduce costs.

[0022] Preferably, the binder comprises polyvinyl alcohol; and the lubricant comprises one or more of tung oil, rapeseed oil and soybean oil.

[0023] In a second aspect, the present invention provides a method for preparing an energy storage ceramic material using shells, comprising the following steps: (1) taking shells, waste soil, sludge and diatomaceous earth in proportion and mixing them evenly to obtain a mixture, adding a binder, a lubricant and water to the mixture, kneading and aging the mixture to obtain a plastic mud; (2) The plastic clay is made into a honeycomb green body by extrusion molding, and a ceramic skeleton containing honeycomb pores is obtained by shaping, drying and firing; (3) uniformly selecting a portion of honeycomb holes in the ceramic skeleton as encapsulation holes, coating one end of the encapsulation holes with an encapsulant, injecting molten salt into the encapsulation holes, and then coating the other end of the encapsulation holes with an encapsulant to obtain a ceramic-molten salt composite; (4) The ceramic-molten salt composite is subjected to heat treatment to obtain energy storage ceramic material.

[0024] Preferably, in step (1), the dry powder of shells, abandoned soil, sludge and diatomaceous earth is obtained by drying the wet materials of shells, abandoned soil, sludge and diatomaceous earth in the open air or at 80°C, crushing them respectively by a fast ball mill, and then passing them through a 250-mesh sieve; the dry powder of shells, abandoned soil, sludge and diatomaceous earth is mixed evenly by a drum ball mill to obtain a mixture.

[0025] Preferably, in step (1), kneading is performed in a vacuum kneader for 0.5 to 2.5 h; and the aging time is 24 to 48 h.

[0026] Preferably, in step (2), in the extrusion molding method, a vertical extruder is used for extrusion molding, and the extrusion molding pressure is 3-6 MPa; the shaping time is 20-40 min; the drying is microwave drying for 1-2 h, the microwave power is 5 kW, and the frequency is 2400 MHz-2500 MHz; the firing process conditions are: the heating rate is 3-5 ℃ / min, the firing temperature is 1000-1200 ℃, and the maximum temperature holding time is 60-180 min; the honeycomb hole is circular. The shaping of the present invention is to fix the extruded green body by air cooling to maintain a stable shape and size, and then remove excess water in the green body by microwave drying, further improve the strength of the green body, and facilitate subsequent firing.

[0027] Preferably, in step (2), the molten salt is obtained by ball-milling one or more of Na2SO4 / NaCl, LiF / MgF2 and Li2CO3 / Na2CO3 for 1 to 2 hours, placing in an alumina crucible, and keeping at 650 to 750°C for 3 to 6 hours. The raw materials are then cooled with the furnace and ball-milled again for 3 to 5 hours, and then sieved through a 500-mesh sieve.

[0028] Preferably, in step (4), the heat treatment conditions are: temperature of 600-700° C., and holding time of 1-2 h.

[0029] In a third aspect, the present invention provides a green refrigeration equipment, see Figure 1 , the equipment includes an electric power system 1, a ceramic heat storage system 2 and a heat energy release refrigeration system 3; The power system 1 includes a power input device 101, which may specifically be a solar photovoltaic power generation device or a valley power input device for inputting solar photovoltaic power generation during the day or valley power generation at night into the ceramic heat storage system.

[0030] The ceramic heat storage system 2 includes a heat preservation layer 201 and an insulating layer 202 arranged in sequence from the outside to the inside. A plurality of electric heating elements 203 and energy storage ceramic materials 204 are evenly and cross-arranged inside the insulating layer 202. The electric heating elements 203 are connected to the power input device 101. The energy storage ceramic material 204 is connected to the heat energy release refrigeration system 3 through a heat exchanger 205. In order to improve the heat exchange efficiency, a gas inlet and a gas outlet are opened on the insulating layer 202, wherein the gas inlet is opposite to one end of the through hole on the energy storage ceramic material 204, and the gas outlet is directly opposite to the heat exchanger 205. By introducing stable air into the insulating layer 202, the air flows from one end of the through hole of the energy storage ceramic material to the other end. The stable high-temperature airflow can make the ceramic absorb and store heat more efficiently to reduce heat loss. The heat exchanger 205 can adopt a fin-tube gas-water heat exchanger, and the high-temperature air discharged from the ceramic heat storage system 2 is used as a heat transfer medium to transfer heat through an indirect connection.

[0031] The heat energy release refrigeration system 3 includes a fan 301 connected to the heat exchanger 205, and the fan 301 is connected to the refrigeration device 302 to provide power to the refrigeration device 302; the heat exchanger 205 is also connected to the water replenishment device 303 through the circulation pump 305 and the water purification device 304.

[0032] The present invention uses the honeycomb energy storage ceramic material encapsulating molten salt as the heat storage material, combines the power system and the heat energy release refrigeration system to prepare a green refrigeration equipment, thereby realizing energy-saving and low-carbon refrigeration with complementary solar energy and valley electricity. The principle and operation process of the equipment of the present invention are described as follows: The solar photovoltaic power generation during the day or valley electricity at night is input into the ceramic heat storage system 2 through the power input device 101 in the power system 1. Under the action of the electric heating element 203, the energy storage ceramic material 204 is heated; the molten salt encapsulated in the energy storage ceramic material 204 undergoes a phase change to complete the heat storage.

[0033] During refrigeration, the heat storage ceramic material 204 completes heat transfer through the heat exchanger 205, so that the cold water in the heat exchanger 205 becomes high-temperature water vapor, which drives the fan 301 to operate and provides power for the operation of the refrigeration device 302. After that, the water vapor will gradually condense, and the lost water will be replenished through the water replenishment device 303 and the water purification device 304, and then under the action of the circulation pump 305, it will re-participate in the circulation of the ceramic heat storage system and the heat energy release refrigeration system (the conversion device is the heat exchanger 205 and the fan 301, which converts the thermal energy into kinetic energy, and then converts the kinetic energy into internal energy), thereby continuously refrigerating or making ice. There are many existing devices or devices that can achieve specific energy conversion, which are not limited here.

[0034] The present invention is further described in detail below through specific embodiments, in which cheap local shells in Hainan, abandoned soil generated by excavation of construction foundation pits, sludge generated by cleaning and dredging rivers and other solid waste resources, as well as low-grade diatomaceous earth are mainly used as raw materials; and a ball mill is used to respectively mill the diatomaceous earth, shells, abandoned soil and sludge, and the raw materials after ball milling are respectively sieved through a 250-mesh sieve to obtain dry powders of each raw material.

[0035] Example 1 In this embodiment, lithium carbonate-sodium carbonate is used as the molten salt. Lithium carbonate (50 wt%)-sodium carbonate (50 wt%) is ball-milled for 1 h to be evenly mixed, then placed in an alumina crucible and heated to 680°C for 3 h to melt. After cooling with the furnace, it is crushed and ball-milled for 4 h, and then passed through a 500-mesh sieve to obtain a mixed salt as molten salt for standby use.

[0036] A method for preparing energy storage ceramic materials using shells, comprising the following steps: (1) According to the mass percentage, 50% shells, 15% waste soil, 10% sludge and 25% diatomaceous earth dry powder were mixed and ball milled for 3 h to obtain a uniform mixture.

[0037] The blank was prepared according to 78 wt% of the mixed material, 20 wt% of water, 2 wt% of tung oil and 4 wt% of polyvinyl alcohol (added), kneaded in a vacuum clay machine for 1 hour, and then aged for 24 hours to obtain a plastic clay.

[0038] (2) The plastic clay was made into a honeycomb green body by extrusion molding, with an extrusion molding pressure of 5 MPa and a pore density of 75%. The molded honeycomb green body was microwave dried for 1.5 h, with a molding time of 30 min, a power of 5 kW, and a frequency of 2500 MHz. The dried green body was then sintered by microwave sintering at a sintering temperature of 1160 ℃, a heating rate of 5 ℃ / min, and a maximum temperature insulation of 120 min. After cooling in the furnace, a ceramic skeleton containing honeycomb pores for encapsulating molten salt was obtained.

[0039] (3) Using the ceramic skeleton obtained in step (2) as the matrix, 3 / 5 of the through holes are uniformly selected as encapsulation holes to encapsulate the molten salt, and the other 2 / 5 of the holes are not encapsulated.

[0040] The specific method is: first, a sealant (titanium iron slag-aluminum dihydrogen phosphate composite sealant, the mass percentages of titanium iron slag and aluminum dihydrogen phosphate aqueous solution are 75% and 25% respectively, and the concentration of aluminum dihydrogen phosphate aqueous solution is 45wt%) is coated on one end of the packaging hole, with a coating thickness of 5 mm, and then molten salt is filled into the hole until 90% of the through hole is filled, and then the same sealant is coated on the other end of the packaging hole to seal the through hole; the process is repeated until 3 / 5 of the packaging holes are encapsulated to obtain a ceramic-molten salt composite.

[0041] (4) Finally, the ceramic-molten salt composite is placed in a muffle furnace and heat treated at 680 °C for 1 h. After cooling in the furnace, the final ceramic-molten salt composite energy storage ceramic material is obtained.

[0042] The specific heat capacity of the sample was tested using a microcalorimeter (C80 microcalorimeter from Setaram, France) in a temperature range of room temperature to 800 °C. The heat storage density was calculated according to formula (1-1):

[0043] Where: Q—heat storage density (kJ / kg); C—specific heat capacity (J / g·K); T0—room temperature (℃); T1—The highest temperature during the test (℃).

[0044] According to tests, the specific heat capacity of the energy storage ceramic material of the present invention at 800°C is as high as 1.76 J / g·K; the heat storage density reaches 1366 kJ / kg (room temperature - 800°C).

[0045] Depend on Figure 2 As shown in the figure, the main crystal orientations of the energy storage ceramic material are wollastonite and cristobalite. The addition of shell powder provides a large amount of CaO, which works together with low-temperature quartz and other impurities to form a liquid phase. As the liquid phase increases, the solubility of quartz in the liquid phase is increased, the temperature required for the quartz crystal transformation is reduced, and the crystal transformation process of quartz is accelerated. Figure 3 As shown, there are a large number of pores in the microstructure and they are evenly distributed, which enables it to encapsulate a large amount of molten salt, thereby improving the heat storage density of the energy storage ceramic material.

[0046] Hot and cold cycle test: The energy storage ceramic material obtained in Example 1 was subjected to a hot and cold cycle test, specifically, the sample was first heated to 800°C, allowed to cool to 200°C, then heated to 800°C again, and then cooled to 200°C. The sample was repeatedly subjected to such a cycle test, with a heating rate of 30°C / min and a cooling rate of 30°C / min.

[0047] After 1500 hot and cold cycle tests, the mass loss of the energy storage ceramic material in Example 1 was only 0.17%. After 7500 hot and cold cycles, the mass loss of the energy storage ceramic material was not large, and the heat storage performance did not decrease significantly, which reflects that the energy storage ceramic material obtained by the present invention has the characteristics of long life.

[0048] Example 2 In this embodiment, sodium sulfate-sodium chloride is used as the molten salt. 70 wt% sodium sulfate and 30 wt% sodium chloride are ball-milled for 2 h to mix evenly, then placed in an alumina crucible and heated to 680°C for 5 h to melt. After cooling with the furnace, the mixed salt is crushed and ball-milled for 4 h and then sieved through a 500-mesh sieve to obtain a mixed salt as molten salt for standby use.

[0049] A method for preparing energy storage ceramic materials using shells, comprising the following steps: (1) According to the mass percentage, 45% shells, 10% waste soil, 10% sludge and 35% diatomaceous earth dry powder were mixed and ball milled for 3 h to obtain a uniform mixture.

[0050] The blank was prepared according to 75 wt% of the mixed material, 22 wt% of water, 3 wt% of tung oil and 2 wt% of polyvinyl alcohol (added), kneaded in a vacuum clay machine for 1 hour, and then aged for 24 hours to obtain a plastic clay.

[0051] (2) The plastic clay was made into a honeycomb green body by extrusion molding, with an extrusion molding pressure of 5 MPa and a pore density of 72%. The molded honeycomb green body was microwave dried for 1.5 h, with a shaping time of 30 min, a power of 5 kW, and a frequency of 2500 MHz. The dried green body was then sintered by microwave sintering at a sintering temperature of 1100 ℃, a heating rate of 5 ℃ / min, and a maximum temperature insulation of 60 min. After cooling in the furnace, a ceramic skeleton containing honeycomb pores for encapsulating molten salt was obtained.

[0052] (3) Using the ceramic skeleton obtained in step (2) as the matrix, evenly select 3 / 5 of the through holes as encapsulation holes to encapsulate the molten salt, and the other 2 / 5 of the holes are not encapsulated. The specific method is: first, coat the encapsulant (titanium iron slag-aluminum dihydrogen phosphate composite encapsulant, the mass percentages of titanium iron slag and aluminum dihydrogen phosphate aqueous solution are 70% and 30% respectively, and the concentration of aluminum dihydrogen phosphate aqueous solution is 50 wt%) on one end of the encapsulation hole, with a coating thickness of 5 mm, then fill the molten salt into the hole until 90% of the through hole is filled, and then coat the other end of the encapsulation hole with the same encapsulant to block the through hole; repeat the process until 3 / 5 of the encapsulation holes are encapsulated to obtain a ceramic-molten salt composite.

[0053] (4) Finally, the ceramic-molten salt composite is placed in a muffle furnace and heat treated at 680 °C for 1 h. After cooling in the furnace, the final ceramic-molten salt composite energy storage ceramic material is obtained.

[0054] After testing (test conditions are the same as above), the specific heat capacity of the energy storage ceramic material obtained in Example 2 at 800°C is as high as 1.64 J / g·K; the heat storage density reaches 1298 kJ / kg (room temperature - 800°C).

[0055] Example 3 In this embodiment, lithium fluoride-magnesium fluoride is used as the molten salt. 60 wt% lithium fluoride and 40 wt% magnesium fluoride are ball-milled for 1.5 h to be evenly mixed, then placed in an alumina crucible and heated to 720°C for 4 h to melt. After cooling with the furnace, the mixture is crushed and ball-milled for 5 h and then sieved through a 500-mesh sieve to obtain a mixed salt as molten salt for standby use.

[0056] A method for preparing energy storage ceramic materials using shells, comprising the following steps: (1) According to the mass percentage, 55% shells, 7.5% waste soil, 7.5% sludge and 30% diatomaceous earth were mixed and ball milled for 3 h to obtain a uniform mixture.

[0057] The blank was prepared according to 80 wt% of the mixed material, 18 wt% of water, 2 wt% of tung oil and 3 wt% of polyvinyl alcohol (added), kneaded in a vacuum clay machine for 1 hour, and then aged for 24 hours to obtain a plastic clay.

[0058] (2) The plastic clay was made into a honeycomb green body by extrusion molding, with an extrusion molding pressure of 5 MPa and a pore density of 70%. The molded honeycomb green body was microwave dried for 1.5 h, with a shaping time of 40 min, a power of 5 kW, and a frequency of 2400 MHz. The dried green body was then sintered by microwave sintering at a sintering temperature of 1200 ℃, a heating rate of 5 ℃ / min, and a maximum temperature insulation of 180 min. After cooling in the furnace, a ceramic skeleton containing honeycomb pores for encapsulating molten salt was obtained.

[0059] (3) Using the ceramic skeleton obtained in step (2) as the matrix, evenly select 3 / 5 of the through holes as encapsulation holes to encapsulate the molten salt, and the other 2 / 5 of the holes are not encapsulated. The specific method is: first, coat one end of the encapsulation hole with an encapsulant (a composite encapsulant of titanium iron slag-aluminum dihydrogen phosphate, the mass percentages of titanium iron slag and aluminum dihydrogen phosphate aqueous solution are 80% and 20%, respectively, and the concentration of aluminum dihydrogen phosphate aqueous solution is 40 wt%), with a coating thickness of 5 mm, then fill the hole with molten salt until 90% of the through hole is filled, and then coat the other end of the encapsulation hole with the same encapsulant to block the through hole; repeat the process until 3 / 5 of the encapsulation holes are encapsulated to obtain a ceramic-molten salt composite.

[0060] (4) Finally, the ceramic-molten salt composite is placed in a muffle furnace and heat treated at 680 °C for 1 h. After cooling in the furnace, the final ceramic-molten salt composite energy storage ceramic material is obtained.

[0061] After testing (test conditions are the same as above), the specific heat capacity of the energy storage ceramic material obtained in Example 3 at 800°C is up to 1.62 J / g·K; the heat storage density reaches 1275 kJ / kg (room temperature - 800°C).

[0062] The energy storage ceramic materials obtained in the above embodiments are used in the green refrigeration equipment of the present invention to realize the cold chain storage and transportation of marine fisheries and fruits and vegetables, that is, the refrigeration temperature is 1 to 5°C and the freezing temperature is -18 to -30°C.

[0063] Comparative Example 1 The only difference from Example 1 is that the molten salt is not encapsulated, and the other steps and conditions are the same as those in Example 1.

[0064] Comparative Example 2 The only difference from Example 1 is that the through holes for encapsulating the molten salt are set to 100% (ie, completely encapsulated), and the other steps and conditions are the same as those in Example 1.

[0065] The results show that the heat storage performance of the ceramic material without molten salt encapsulation in Comparative Example 1 is poor, while the molten salt in Example 1 can increase the heat storage density through the latent heat of phase change after being introduced into the honeycomb ceramic as a phase change material, thereby improving the heat storage capacity of the energy storage ceramic material; and the molten salt has a large latent heat of phase change, which can provide a long-term constant temperature heat source, so that the temperature of the heat exchange medium at the outlet is stable, which is conducive to the stable operation of the refrigeration device. When the through holes for encapsulating molten salt in Comparative Example 2 are set to 100%, although the ceramic material has a better heat storage capacity at this time, there are no extra through holes as heat exchange channels for the ceramic material, and the integration of heat storage and efficient heat exchange of the ceramic material cannot be achieved.

[0066] In Examples 1-3, the unencapsulated through holes in the energy storage ceramic material account for 2 / 5. At this time, the heat exchange efficiency of these energy storage ceramic materials is the highest. The high-temperature air flows from one side of the channel to the other side, and releases heat through convection heat exchange with the honeycomb ceramic wall. The encapsulated molten salt absorbs heat through heat conduction with the tube wall, making the heating rate of the molten salt faster. Therefore, the present invention preferably encapsulates molten salt in 3 / 5 through holes.

[0067] In summary, the present invention has the following advantages: 1. The energy storage density of the energy storage ceramic material of the present invention is relatively high. The present invention utilizes the natural porous structure of shells and is combined with porous materials such as diatomaceous earth to make the fired energy storage ceramic matrix dense and porous in structure. Then, by encapsulating molten salt, its high-temperature heat storage capacity is further improved, so that the heat storage per unit volume is relatively high, and green refrigeration equipment can have a larger refrigeration capacity without occupying a large area, thereby reducing investment and land occupation.

[0068] 2. The green refrigeration equipment of the present invention has the characteristics of stable refrigeration effect, long life and excellent environmental protection benefits. Due to the structural characteristics of the honeycomb ceramic heat storage body, it can work stably for a long time, generally has a lifespan of 20 years, and can withstand relatively high temperatures (800°C). In addition, the present invention uses island waste shells, waste soil, etc. as the main raw materials, with a high utilization rate. The energy storage honeycomb ceramics made from them are used in green refrigeration equipment, which is expected to consume waste shells and waste soil on a large scale, and therefore has the benefit of environmental protection.

[0069] 3. The refrigeration equipment of the present invention has the characteristics of low carbon and low cost. The present invention uses solar energy and off-peak electricity as the main driving energy. Compared with conventional refrigeration equipment using fossil energy or peak electricity, the refrigeration cost can be reduced by 30-50% and the carbon emission can be reduced by 30%.

[0070] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. An energy storage ceramic material prepared using shells, characterized in that: It includes a ceramic skeleton containing honeycomb pores, and a molten salt encapsulated in the honeycomb pores of the ceramic skeleton by an encapsulant; The raw materials of the ceramic skeleton include a main material and a binder accounting for 2 to 6% of the mass of the main material; In terms of mass percentage, the main material includes 68-80% of a mixed material, 2-6% of a lubricant, and 14-30% of water; The mixed material comprises shells, waste soil, sludge and diatomaceous earth.

2. The energy storage ceramic material prepared using shells according to claim 1, characterized in that: Calculated by mass percentage, the mixture includes 10-80% shells, 5-30% abandoned soil, 5-30% sludge, and 10-80% diatomaceous earth; the shells, abandoned soil, sludge and diatomaceous earth in the mixture are all dry powders after passing through a 250-mesh sieve.

3. The energy storage ceramic material prepared using shells according to claim 1, characterized in that: Calculated in terms of the mass percentage of oxides, the main components of shells are CaO: 40-60%, loss on ignition: 40-60%; the main components of abandoned soil are SiO2: 50-60%, Al2O3: 15-25%, CaO: 7-9%, Fe2O3: 2-3%, MgO: 3-4%, K2O: 1-2%; the main components of sludge are SiO2: 50-70%, Al2O3: 5-20%, loss on ignition: 30-50%; the main components of diatomaceous earth are SiO2: 75-95%, Al2O3: 5-25%, Fe2O3: 0-5%.

4. The energy storage ceramic material prepared using shells according to claim 1, characterized in that: The pore density of the honeycomb holes in the ceramic skeleton is 70-80%; 50-67% of the honeycomb holes in the ceramic skeleton are uniformly selected to inject molten salt for packaging; in a single honeycomb hole, the injected volume of the molten salt is 85-92% of the volume of the honeycomb hole.

5. The energy storage ceramic material prepared using shells according to claim 1, characterized in that: The molten salt includes one or more of Na2SO4 / NaCl molten salt, LiF / MgF2 molten salt and Li2CO3 / Na2CO3 molten salt; In terms of mass percentage, the encapsulant is a composite of 70-80% titanium iron slag and 20-30% Al(H2PO4)3 aqueous solution, the concentration of the Al(H2PO4)3 aqueous solution is 40-50wt%; the coating thickness of the encapsulant is 3-7mm; The binder includes polyvinyl alcohol; the lubricant includes one or more of tung oil, rapeseed oil and soybean oil.

6. The method for preparing the energy storage ceramic material according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) taking shells, waste soil, sludge and diatomaceous earth in proportion and mixing them evenly to obtain a mixture, adding a binder, a lubricant and water to the mixture, kneading and aging the mixture to obtain a plastic mud; (2) The plastic clay is made into a honeycomb green body by extrusion molding, and a ceramic skeleton containing honeycomb pores is obtained by shaping, drying and firing; (3) uniformly selecting a portion of honeycomb holes in the ceramic skeleton as encapsulation holes, coating one end of the encapsulation holes with an encapsulant, injecting molten salt into the encapsulation holes, and then coating the other end of the encapsulation holes with an encapsulant to obtain a ceramic-molten salt composite; (4) The ceramic-molten salt composite is subjected to heat treatment to obtain energy storage ceramic material.

7. The method for preparing the energy storage ceramic material according to claim 6, characterized in that: In step (1), kneading is performed in a vacuum kneading machine for 0.5 to 2.5 h; and the aging time is 24 to 48 h.

8. The method for preparing the energy storage ceramic material according to claim 6, characterized in that: In step (2), in the extrusion molding method, a vertical extruder is used for extrusion molding, and the extrusion molding pressure is 3 to 6 MPa; The shaping time is 20 to 40 minutes; the drying is microwave drying for 1 to 2 hours, the microwave power is 5 kW, and the frequency is 2400 MHz to 2500 MHz; The sintering process conditions are: a heating rate of 3 to 5 °C / min, a sintering temperature of 1000 to 1200 °C, and a holding time of 60 to 180 min; The molten salt is obtained by ball-milling one or more of Na2SO4 / NaCl, LiF / MgF2 and Li2CO3 / Na2CO3 for 1 to 2 hours, placing in an alumina crucible, keeping at 650 to 750°C for 3 to 6 hours, then ball-milling the raw materials cooled with the furnace for 3 to 5 hours again, and passing through a 500-mesh sieve.

9. The method for preparing the energy storage ceramic material according to claim 6, characterized in that: In step (4), the heat treatment conditions are: temperature of 600-700°C and holding time of 1-2 h.

10. A green refrigeration equipment, characterized in that: It includes power system, ceramic heat storage system and heat energy release refrigeration system; Wherein, the power system is used to input solar photovoltaic power generation during the day or valley electricity at night into the ceramic heat storage system; The ceramic heat storage system comprises a heat preservation layer and an insulating layer arranged in sequence from the outside to the inside, a plurality of electric heating elements and the energy storage ceramic material according to any one of claims 1 to 5 are evenly and cross-arranged inside the insulating layer, and the electric heating elements are connected to the power system; The energy storage ceramic material is connected to a heat energy release refrigeration system through a heat exchanger, and the heat energy release refrigeration system is used to convert thermal energy into refrigeration kinetic energy.

Citation Information

Patent Citations

  • A preparing method of an inorganic phase-change insulating building material

    CN106167372A

  • Used heat refrigeration is equipped

    CN205536660U

  • Environment-friendly energy-saving heating and refrigerating equipment

    CN212299486U